Calculated structures and energies of molecular crystals using dispersion corrected density functionals - Carter, Damien; Rohl, Andrew (2014)
Input, output and pseudopotential files for SIESTA and Quantum ESPRESSO calculations of the structures and energies of the S22 reference set of molecular complexes, the C21 and C19RT reference sets of molecular crystals and the the monosaccharides with experimentally determined crystal structures. The calculations utilise the vdW-DF, vdW-DF2 and XDM functionals with both small and large basis sets.